2001
DOI: 10.1016/s0266-352x(00)00020-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification of soil parameters by inverse analysis

Abstract: International audienceThis paper presents a methodology for identifying soil parameters that takes into account different constitutive equations. The procedure, applied here to identify the modified Cam-Clay parameters from a pressuremeter curve, is based on an inverse analysis approach, which consists of minimizing the function representing the difference between the experimental data and the data obtained by integrating the model along the loading path in in-situ testing. The numerical process implemented he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 4 publications
1
56
0
2
Order By: Relevance
“…Therefore, the identification of the compressibility by inverse analysis becomes impossible since a large range of compressibility factors leads to the same pressure-volume curve. Zentar et al [5], then Rangeard et al [6] suggested methods to identify simultaneously two or three other parameters of the modified Cam-Clay model in clays. For instance, Zentar et al [5] succeeded in determining the couples ðG; MÞ or ðG; p 0 c0 Þ from one pressuremeter curve obtained in undrained conditions and in determining the couple ðM; p 0 c0 Þ from one pressuremeter curve in drained conditions.…”
Section: Pressuremeter Test Results In Claysmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the identification of the compressibility by inverse analysis becomes impossible since a large range of compressibility factors leads to the same pressure-volume curve. Zentar et al [5], then Rangeard et al [6] suggested methods to identify simultaneously two or three other parameters of the modified Cam-Clay model in clays. For instance, Zentar et al [5] succeeded in determining the couples ðG; MÞ or ðG; p 0 c0 Þ from one pressuremeter curve obtained in undrained conditions and in determining the couple ðM; p 0 c0 Þ from one pressuremeter curve in drained conditions.…”
Section: Pressuremeter Test Results In Claysmentioning
confidence: 99%
“…The second point concerns previous works done on the interpretation of pressuremeter tests for determining the Cam-Clay parameters [5,6]. A methodology was developed for identifying simultaneously mechanical Cam-Clay parameters and permeability from pressuremeter tests with strain holding stages.…”
Section: Determination Of the Compressibility From Pressuremeter Testsmentioning
confidence: 99%
“…In this case, due to the non homogeneous stress paths, a more sophisticated inverse analysis is required. Many studies have been conducted on pressuremeter tests in order to characterize soil parameters (Mehta, 1989;Cambou and Bahar, 1993;Ledesma et al, 1996;Schnaid and Mantaras, 1998;Zentar et al, 2001;Dano et al, 2007;Rechea et al, 2007). Inverse analysis consists in minimizing the difference between experimental data collected in situ and the predictions of analytical or numerical calculations (Figure 1).…”
Section: Inverse Analysis Of Field Tests In the Geotechnical Areamentioning
confidence: 99%
“…Dentre as principais técnicas aplicadas em geotecnia destaca-se o algoritmo genético (AG) proposto por Holland (1992), um mecanismo de busca adaptativa que se baseia no princípio Darwiniano de seleção natural e reprodução genética. Jin et al (2016) destacam que devido a sua robustez, eficiência e capacidade de fornecer um conjunto de soluções próximas da solução ideal ao invés de uma única resposta, o que o torna mais prático do ponto de vista geotécnico, faz do AG uma das técnicas mais aplicadas para solução dos problemas em geotecnia (SAMARAJIVA; MACARI; WATHUGALA, 2005;LEVASSEUR et al, 2008;BAROTH;MALECOT, 2010;ROKONUZZAMAN;SAKAI, 2010;HELENO, 2011;PAPON, 2012;JIN et al, 2016;YIN et al, 2017) Dentro desse contexto, utilizar os resultados de medições diretas possíveis de serem feitas no campo para, por meio de análises inversas, estimar parâmetros de modelos constitutivos de comportamento do solo é um caminho que tem se mostrado promissor (LEDESMA; GENS; ALONSO, 1996;ZENTAR;MOULIN, 2001;FINNO, 2004;CALVELLO, 2005;LEVASSEUR et al, 2008;HICHER, 2008;BAROTH;MALECOT, 2010;HELENO, 2011;PAPON, 2012;ZHAO et al, 2015;YIN et al, 2017).…”
Section: -Introduçãounclassified